2016
DOI: 10.18632/oncotarget.10363
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ERα/ERK/P62 cascades induces “autophagic switch” in the estrogen receptor-positive breast cancer cells exposed to gemcitabine

Abstract: Several clinical trials revealed that estrogen receptor (ER) status had relevance to the response of mammary malignancy to chemotherapy. Autophagy has emerged as an important cellular mechanism of tumor cells in response to anticancer therapy. The aim of this study is to investigate whether gemcitabine induces autophagy, and more importantly, whether such autophagy is functional relevant to the therapeutic effects of gemcitabine in breast cancer cells in relation to the ER status. In our study, autophagy was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Studies have found that phosphorylation of Erk induces autophagy in human cervical cancer Hela cells (31) and liver cancer cells (22). We found that 40 nmol/l TPI could increase p-p38 MAPK and p-Erk expression after treatment for 24 h. Erk activation is closely related to autophagy induction (16,30,32). When combined with Erk inhibitor U0126, as shown in Fig.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Studies have found that phosphorylation of Erk induces autophagy in human cervical cancer Hela cells (31) and liver cancer cells (22). We found that 40 nmol/l TPI could increase p-p38 MAPK and p-Erk expression after treatment for 24 h. Erk activation is closely related to autophagy induction (16,30,32). When combined with Erk inhibitor U0126, as shown in Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Phosphorylated Erk1/2 can suppress cell growth, and also promotes the expression of Beclin-1 (30). Studies have found that phosphorylation of Erk induces autophagy in human cervical cancer Hela cells (31) and liver cancer cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the differences response to starvation in ATG genes described above likely contribute to the targeted therapy of breast cancer. It has been reported that ER status is relevant to the difference in autophagic response in breast cancer (Shen et al 2016 ), however, whether the specific role of these genes depends on ER status in anti-cancer therapy needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, deregulation of autophagy has been linked to several organismal pathologies including cancer (Levine & Kroemer 2008 ; Mowers et al 2017 ). Recently, it has been shown that autophagy plays a pivotal role in growth, metastasis and invasion of breast cancer (Zhou et al 2016 ), and the function of autophagy is distinct in different breast cancer subtypes, for example, cytoprotection in MDA-MB-231 cells and cytotoxicity in MCF-7 cells has been observed during gemcitabine-induced autophagy (Shen et al 2016 ). Therefore, the adaptive regulation of autophagy could augment the effects of anti-cancer therapy in breast cancer (Rebecca & Amaravadi 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy alteration may be another contributing factor [ 18 ]. Gemcitabine can activate autophagy in different types of cancer cells such as that of bladder cancer [ 19 ], breast cancer [ 20 , 21 ] and pancreatic cancer [ 22 , 23 ]. The role of autophagy in a cell's fate is cell or tissue type-specific, and depends on stimuli, activation duration and intensity, and related signaling [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%